2020
DOI: 10.1136/oemed-2020-106956
|View full text |Cite
|
Sign up to set email alerts
|

Mask-associated ‘de novo’ headache in healthcare workers during the COVID-19 pandemic

Abstract: ObjectivesThe pandemic caused by the new coronavirus (COVID-19) has changed care activities of health professionals. We analysed the possible association between the appearance of ‘de novo’ headache according to the type of mask used, the related factors and the impact of the cephalalgia on health professionals.MethodsCross-sectional study in a tertiary hospital in Extremadura, Spain. We provided an online questionnaire to healthcare workers during the period of maximum incidence of COVID-19 in our setting.Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 31 publications
7
38
0
2
Order By: Relevance
“…Our study findings are in close agreement with the study of Ramirez-Moreno JM et al who reported 51.6% PPE associated "de novo" headache in Spain in 2020 (19) . In the study of Ong JJY et al, newly developed headache occurrence after using PPE was 82% (9) .…”
Section: Resultssupporting
confidence: 93%
“…Our study findings are in close agreement with the study of Ramirez-Moreno JM et al who reported 51.6% PPE associated "de novo" headache in Spain in 2020 (19) . In the study of Ong JJY et al, newly developed headache occurrence after using PPE was 82% (9) .…”
Section: Resultssupporting
confidence: 93%
“…Auflage in die Klassifikation aufgenommen, damals aber noch nicht als primär, sondern als Neuralgie klassifiziert worden [64]. Unklar ist, ob auch der Anstieg des CO 2 -Partialdrucks zum Auftreten der Kopfschmerzen beitragen könnte, auch wenn das Tragen einer Maske nicht zu Hyperkapnie führt [63,65].…”
Section: Auswirkungen Von Pandemie Und Quarantäne Auf Kopfschmerzenunclassified
“…Die COVID-19-Pandemie weckte erhebliches Forschungsinteresse, das zu einem rasanten Wissensanstieg führte. Besonders wichtig erscheint uns gerade auch im Hinblick auf die Zeit nach der Quarantäne, dass sich eine Migräneerkrankung durch eine flexible Alltagsgestaltung und Verringerung der Verpflichtungen positiv beeinflussen lässt [62,63]. Auch wenn die gute Wirkung der nicht-medikamentösen Migränebehandlung schon länger bekannt ist [66], haben Home-Office und Gleitzeit noch keinen Eingang in die Therapieempfehlungen gefunden.…”
Section: Ausblickunclassified
“…200 Indeed, studies suggest applying a splint induces myofibroblasts, 80 and pony-tails/hijabs/braziers appear to cause myofascial pain. [201][202][203][204][205] This phenomenology looks to be a similar or the same as that of applying bandages to "rheumatism" patients (William Balfour 1815), 206 meaning: modulation of the tensegrity structure and/or induction of stress shielding but failing to resolve tension (eg, Mrs. M. Pages 179-180). Interestingly, experimental models of restraint stress apply mechanical restraint and/or limit movements.…”
Section: Bizarrely Wang Et Al Find a Bidirectional Association Between Fibromyalgia And Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 99%